Challenges Faced by Teacher in Teaching English at SMP Negeri 1 Bonggakaradeng - Somakanna, Sucian; Pongsapan, Nehru; Allo, Markus Deli Girik (Universitas Cokroaminoto Palopo, 2023)
This study explores the challenges faced by an English teacher at SMP Negeri 1 Bonggakaradeng, a rural junior high school in Tana Toraja, Indonesia, and the strategies employed to overcome them. Using a qualitative case study approach, data were collected through classroom observations and semi-structured interviews. Findings reveal that teaching English in this context is hindered by students’ limited vocabulary, low motivation, diverse learning needs, scarce resources, and limited exposure to English outside the classroom. In response, the teacher applied adaptive strategies such as differentiated instruction based on student interests, the integration of visual and multimedia tools, and game-based learning. Although innovative methods improved student engagement and language acquisition, challenges like time constraints in producing learning media remained. The study highlights the need for systemic support, including professional development and access to educational technology, to enhance teaching effectiveness and bridge rural-urban disparities in English education.